(untitled) - Drucker., Peter F. (New York, 1999)
Contents: Management's new paradigms, strategy - the new certainties; the change leader, information challenges, knowledge-worker productivity, managing oneself,...
Keywords: Management,Twenty-first century,Quản trị,Thế kỷ 21; Forecasting,Forecasts,Dự báo,Dự báo